"It's What's on the Inside That Counts": A Pilot Study of the Subjective Changes among Returned Citizens Participating in a Peer-Mentor Support Initiative. Issue 46 (1st November 2020) - Lopez-Humphreys, Mayra; Teater, Barbra
Abstract: Peer mentorship programs with returned citizens (i.e., formally incarcerated) have recently emerged as a model that provides mentees and mentors with opportunities to practice new roles that broaden their self-identity and consequently can also assist with maintaining ongoing, non-recidivating behavior. Yet, few evidence-based models focus directly on supporting the peer mentor's identity change process. This study employed a pretest–posttest evaluation of a pilot six-week training program, the Credible Messengers Institute, designed to support subjective factors that strengthen the self-identity change process among returning citizens ( N = 35) who are mentoring adjudicated youth. Findings revealed a statistically significant improvement in subjective factors, including, self-esteem, level of hope, and elements of self-identity change behaviors (self-knowledge; self-awareness and self-reflection; self-care) from pretest to posttest. The issue of developing the self-identity of returned citizens contributes to a wider discussion on the challenges and recent trends in the development of post-incarceration services and supports. Future research should replicate this pilot study with additional participants and rigorous research methodologies to further substantiate the subjective changes among peer mentors.